Book Review: D. KOROBEINIKOV, Byzantium and the Turks in the Thirteenth Centruy, Oxford 2014, pp. xxi+372. ISBN 978-0-19-870826-1 - ΚΥΡΙΤΣΗΣ, Δημήτρης (Byzantina Symmeikta, 2016)
Book Review: D. KOROBEINIKOV, Byzantium and the Turks in the Thirteenth Centruy, Oxford 2014, pp. xxi+372, ISBN 978-0-19-870826-1